What Now for Australia's NBN? How Australia's politics, insular policies and preference for monopolies have made Australia a broadband backwater - McLaren, Gary (Journal of Telecommunications and the Digital Economy, 2018)
Australia, like other countries, embarked on deregulation and privatisation of its telecommunications market in the late 1980s. The success of infrastructure competition in the mobile communications sector in pushing Australia to being a world leader in that sector contrasts with the failure to achieve the same in fixed telecommunications. Australia’s politics, insular policies and categorisation of fixed telecommunications as a natural monopoly have made Australia a global laggard in the provision of broadband services. The return of government ownership of telecoms infrastructure in the form of the National Broadband Network and the continuing lack of investment in fibre infrastructure highlight the political and policy failures that have accumulated. A disaggregation of NBN Co into competing technology-based entities, along with the establishment of a regional telecommunications fund financed by a broad-based telecommunications levy, is recommended as the answer to fix these long-term problems.